2019
DOI: 10.7888/juoeh.41.375
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Noise Annoyance and Cognitive Performance in Automotive Workers Exposed to Chronic Noise

Abstract: Among the most important complaints of people exposed to noise are the feelings of resentment and annoyance, and the changes in mental conditions, which are among the main psychological consequences affecting the concentration and accuracy of workers. This study was designed to investigate the relationship between annoyance and cognitive performance of workers exposed to chronic noise. This is a descriptive-analytical study conducted on workers in an automotive company. Three hundred workers exposed to noise w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…20 Furthermore, it has been reported that the benefits of napping depends on the duration and circadian placement of the nap. 21 Moreover, cognitive performances are influenced by activity or other stimuli, such as physical activity, [22][23][24] light 25 or noise 26 exposure. To the best of our knowledge, no meta-analysis has assessed the benefits of napping on objective cognitive performance during night shifts.…”
Section: Introductionmentioning
confidence: 99%
“…20 Furthermore, it has been reported that the benefits of napping depends on the duration and circadian placement of the nap. 21 Moreover, cognitive performances are influenced by activity or other stimuli, such as physical activity, [22][23][24] light 25 or noise 26 exposure. To the best of our knowledge, no meta-analysis has assessed the benefits of napping on objective cognitive performance during night shifts.…”
Section: Introductionmentioning
confidence: 99%
“…They suggested that hearing loss af-fected the neuro-brain system, which is related to speech. Moreover, a study by Alimohammadi et al (29) on the effects of noise annoyance on cognitive function showed a significant relationship between noise annoyance and cognitive function of workers chronically exposed to noise. The researchers also indicated that noise annoyance was associated with reduced mental performance of the workers, resulting in an increased risk of job errors.…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, it should be noted that the mean differences between Active and Sham groups fall within this reliability range at all frequencies tested ( Table 2 ). To this end, it is worth noting that elevated levels of distress and reduced concentration following noisy exposures has shown to affect performance in perceptual tasks which could attempt to explain these subtle differences ( 29 ). Additionally, it has been shown that adaptations to sound perception can occur following high-level acoustic exposure lessening one’s sensitivity, and therefore rendering low-level sounds less detectable following noise (i.e., when post-noise testing was conducted).…”
Section: Discussionmentioning
confidence: 99%